Degree of Information Security at Telecommunications Sector in Yemen - Nabil Hassan Abdo Al-Hemyari (University of Science and Technology, Sanaa, Yemen, 2023)
This study aimed to determine the degree of information security (confidentiality, integrity, availability) at telecommunications sector in Yemen. To achieve this, the descriptive method was followed and a questionnaire was used for collecting data from the study sample at telecommunications sector, which includes the six telecommunication companies and Public Telecom Corp. The sample was selected by the complete census method. The questionnaire forms were distributed to (356) participants; however, only (218) forms were valid for analysis. The data were analyzed by the Statistical Package for the Social Sciences (SPSS) program. The study findings revealed that the degree of information security at telecommunications sector in Yemen was high; the degree of confidentiality was the highest, followed by integrity, then availability. The study recommended that the information security should be reinforced, and procedures for protecting information from disclosure or modification, as well as activities for authorized access to information and services should be supported.